Religious Moderation in Practice: A Framing Analysis of Nonformal Hajj Education and Its Global Relevance - Marsudi; Nina Mariani Noor (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2025)
Religious moderation has emerged as a central discourse in strengthening social cohesion and countering the rise of exclusivist and radical narratives in Muslim-majority societies. While formal education has been widely explored in this regard, the contribution of nonformal settings such as Islamic pilgrimage guidance institutions remains underexamined. This study investigates how the nonformal religious education practices of KBIH ’Aisyiyah Bantul integrate religious moderation values tolerance, anti-violence, balance, and accommodation of local culture through a framing approach. Drawing on qualitative methods, including in-depth interviews, participant observation, and document analysis, the research highlights the institutional strategies in embedding moderation during Hajj preparation and community-based religious activities. The analysis employs frame theory to uncover how moderation values are articulated, negotiated, and internalized within the educational process. Findings demonstrate that KBIH ’Aisyiyah Bantul frames religious moderation as both a theological imperative and a socio-cultural necessity, aligning with broader efforts in Indonesian Islamic education reform. Moreover, the results reveal that digital learning spaces and e-learning platforms extend the reach of moderation discourse, while pilgrimage experiences situate moderation within global encounters of diversity and communitas. These insights underscore the potential of nonformal education to complement formal curricula in shaping inclusive religious identities. The study’s global relevance lies in showing how localized practices of religious moderation can contribute to international debates on peacebuilding, intercultural dialogue, and resilience against radicalism. Implications are offered for policymakers, educators, and faith-based organizations seeking to foster sustainable models of moderation in religious education worldwide.